Bringing MDMA-assisted therapy for PTSD to traditional healthcare systems: tending to set and setting - Perivoliotis, Dimitri; Knopp, Kayla; Remick, Shannon; Kaigle, Allie; Stauffer, Christopher S.; Khalifian, Chandra; Wachsman, Tamara R.; Chargin, Bettye E.; Bismark, Andrew W.; Alam, Al; Morland, Leslie (Frontiers in Psychiatry, 2025)
Although effective evidence-based trauma-focused psychotherapies for posttraumatic stress disorder (PTSD) are available, a significant proportion of patients show a suboptimal response or do not complete them. MDMA-assisted therapy (MDMA-AT) for PTSD is a promising intervention currently being evaluated in numerous studies worldwide, including investigation for potential Food and Drug Administration (FDA) approval in the United States. The concepts of set and setting are foundational in psychedelic therapy and refer to the mindset a person brings to therapy and the environment in which it takes place, respectively. Both are believed to play a critical role in the individual’s experience and efficacy of MDMA-AT. In this article, we describe the importance of set and setting in MDMA-AT for PTSD and outline the advantages and challenges of implementing this novel intervention in large healthcare settings such as the Veterans Health Administration (VHA). Mostly derived from our experience conducting clinical trials of MDMA-AT for PTSD in VHA, we present specific and practical suggestions for optimizing set and setting from both the participant’s and clinician’s perspective in a manner that both leverages the opportunities of such settings and adapts to their challenges. These recommendations are intended to inform future MDMA-AT for PTSD research and, potentially, eventual clinical implementation efforts in traditional healthcare systems.